Women’s preferences for maternal healthcare services in Bangladesh: Evidence from a discrete choice experiment. - Mahumud, Rashidul Alam; Alamgir, Nadia Ishrat; Hossain, Md. Tarek; Baruwa, Elaine; Sultana, Marufa; Gow, Jeff; Alam, Khorshed; Ahmed, Syed Masud; Khan, Jahangir A.M. (MDPI, 2022)
This article was published in The Journal of Clinical Medicine [© This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited] and the definite version is available at: https://doi.org/10.3390/jcm8020132 The Journal's website is at: https://www.mdpi.com/2077-0383/8/2/132